Optimization the Management of Tihu Village Resources to Increase the Income of Village Communities: Optimalisasi Pengelolaan Sumber Daya Desa Tihu untuk Meningkatkan Penghasilan Masyarakat Desa - La Ode Nashar Nashar; Novianita Achmad Novianita; Nisky Imansyah Yahya Nisky (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Geographically Tihu village is located on the coast where the majority of its residents work as fishermen. Skipjack tuna is a type of fish that is abundant in Tihu village. The habit of fishermen distributing their catch to consumers causes the economic value of sales to be less than optimal. Processing skipjack tuna into shredded fish and nuggets will support the increased income of the society of Tihu village. This society service provides training to the Tihu village society to make floss, nuggets and coconut cookies according to BPOM standards as well as packaging and online marketing method. This training was carried out so that the Tihu village society could optimize their natural resources to increase their income.